Assessing the Impact of YouTube Video Tutorials on Procedural Text Writing Skills - Ichsan, Ichsan; Darmawan; Eisenring, Moh. Abraham Akbar; Dewi, Anjar Kusuma Dewi (LPPM Universitas Advent Indonesia, 2025)
Objective of the research aims to find out find out whether or not using YouTube video tutorial is effective in improve tenth grade students’ skill in writing procedure text at MAN 2 Kota Palu. Many students have problems achieving this skill for various reasons: limited understanding, lack of vocabulary, low creativity of the students. This research used a quantitative method and quasi-experimental as the research design. The data was collected by taking pre-test and post-test. This study used purposive sampling with the sample was XA as the control group and XB as the experimental group. Based on the result, the post test of experimental class was 75.72, it was lower than control group was 75.76. Therefore, Then, the result of statistical hypothesis testing by using Mann-whitney U showed that 0.857 > 0.05). It means that there was not a significant distinction between the groups. This research conclude that YouTube video tutorials was not effective in improving students’ skill in writing procedure text among tenth grade students at MAN 2 Kota Palu. The suggestions of the research are knowing students' learning style, providing clear guidance, and exploring potential alternatives media.